Case Study On Maritime Academy Of Malaysia - Jaafar, Gazali (2006)
Akademi Laut Malaysia (ALAM) was established as an academy for the development and enhancement of the education and training of Merchant Navy Officers and Ratings. It was functioning under the control and supervision of MATES Foundation, a company limited by guarantee and not having a share capital.